Testing the spatial auto-regression (SAR) model on Indonesia's regional economy - Firman Herdiansah; Setyo Tri Wahyudi (Jurnal Ekonomi Pembangunan, 2020)
Indonesia's regional economy that is proxy by using Gross Regional Domestic Product (GRDP) per capita to form clusters is investigated. Besides, by using the Spatial Auto-regression (SAR) model, the effect of household consumption in a region to the surrounding area's economy is examined. The study on this topic is rather limited, especially in the regional economic development of the country. Furthermore, Indonesia is a heterogeneous country, and its consequence is that development policy should consider the geographic characteristics of the country. The results show that there are regional economy clusters in Java, Kalimantan, Sulawesi, and Sumatra. In contrast, household consumption in a region has a weak influence on the economy in the surrounding area.